THE EFFECTIVENESS OF PHOSPHATE SOLUBALIZING BACTERIA AS BIOCONTROL AGENTS - G. Z. Jahangir; M. Sadiq; N. Hassan; I. A. Nasir; M. Z. Saleem; M. Iqbal (Journal of Animal and Plant Sciences, 2016)
Phosphorus is considered among most vital macro-elements, which is mandatory for successful plant growth. Although it is plentiful in soil both in its organic and inorganic form but its larger fraction is unavailable to plants. Different phosphate solubilizing micro-organisms (PSMs) residing in soils can change the chemical nature of these organic and inorganic phosphate compounds and make them available to plants. Only bacteria are focus of this study which investigates the antifungal potential of these phosphate solubilizing bacteria (PSB). These    These PSB can perform important role in defending plant roots from pathogenic fungi in an environment friendly mode. Hence, help in minimizing the dependence on environmentally harmful and expensive phosphate fertilizers and fungicides. From a plenty of purified PSB isolates only elite strains with higher phosphate solubilization index have been selected for identification and for bio control studies. Alternaria alternate (A. alternate ), Macrophomina phasiolina (M. phasiolina), Fusarium oxysporum (F. oxysporum) and Sclerotium rolfsii (S. rolfsii) had been grown simultaneously along with six selected PSB strains including Burkholederia cepacia (B. cepacia), Citrobacter freundii (C. freundii ), Enterobacter aerogenes (E. aerogenes), Klebsiella pneumonia (K. pneumonia), Proteous vulgaris (P. vulgaris) and Acinetobacter lwoffi (A. lwoffi). The completely restricted growth of mycelia of these plant pathogenic fungi was observed in the presence of selected bacterial strains which have been found as effective bio control agents. The results of the presented work strongly encourage the need to explore more PSB strains with higher phosphate solubilizing potential and deadly effective against broader range of plant pathogenic fungi.
Keywords: Bio control; Phosphate solubilizing bacteria; rhizosphere soil; plant pathogens